(untitled) (Bangladesh Journal of Agricultural Research, 2013)
Tricho-compost, a Trichoderma based compost fertilizer, was developed by mixing a definite concentration of spore suspension of a Trichoderma harzianum strain with measured amounts of processed raw materials, such as cowdung, poultry refuse, water hyacinth, vegetable wastes, sawdust, maize bran, and molasses. Tricho-leachate, a liquid by-product of the Tricho-compost, was obtained during decomposition of Tricho-compost materials. These bioproducts were tested both in the laboratory and in seedbed nurseries to evaluate their effectiveness against soil-borne pathogens for growing cabbage seedlings. Application of Tricho-compost and Tricho-leachate reduced the seedling mortalities of cabbage caused by Sclerotium rolfsii by about 98%. In laboratory tests, Trichoderma harzianum, after re-isolation from Tricho-compost and tricho-leachate, was also found to be highly effective to arrest the growth of S. rolfsii. T. harzianum destroyed the radial growth of S. rolfsii mycelium by 59.7% after five days, and effected total destruction of the mycelium in 10 days. In seedbed nurseries, soil applications of Tricho-compost and Tricho-leachate significantly increased the seedling germination rate and reduced the incidence of soil-borne diseases and infestation of root-knot nematodes. Field experiment showed that combined application of Tricho-compost and Tricho-leachate reduced the seedling mortalities by 40.9% to 64.5% in Gazipur and 53.3% to 62.1% in Bogra. Application of Tricho-leachate at 500 ml per sq. metre increased plant weight by about 55.6%, and reduced the seedling mortality by about 84.0% in Gazipur. Seedbed nurseries treated with Tricho-compost and Tricho-leachate had only Pythium spp as a soil-borne pathogen, whereas the control plot had as many as four soil-borne pathogens -Pythium, Rhizoctonia, Sclerotium and Fusarium spp. Use of richo-compost and Tricho-leachate also reduced the infestation of root-knot nematode by about 80.7% to 91.0%. The results clearly showed that use of Tricho-compost and Tricho-leachate is highly effective for production of healthy cabbage seedlings. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14390 Bangladesh J. Agril. Res. 37(4): 653-664, December 2012